Women and Letterpress Printing 1920-2020 Gendered Impressions - Battershill, Claire (Humanities, 2022)
This Element analyses the relationship between gender and literary letterpress printing from the early 20th century to the beginning of the 21st. This title is also available as Open Access on Cambridge Core.